Bridging the Economic Divide: Transnational Educational Frameworks and Wealth Creation in Developing Economies - Mingyu Duan; Ten Ho (Outline Publisher, 2026)
The persistent economic divide prompted developing nations to adopt transnational educational frameworks as a mechanism to cultivate human capital and arrest intellectual capital flight. This study investigated the empirical relationship between localized transnational education and grassroots wealth creation in emerging economies. The researchers utilized a quantitative explanatory design, collecting primary survey data from 412 alumni of cross-border degree programs operating within developing host countries. The study evaluated the structural relationships using partial least squares structural equation modeling. The empirical analysis revealed that participation in transnational education significantly fostered the acquisition of globally competitive human capital and actively stimulated domestic entrepreneurial intentions. Furthermore, institutional linkages embedded within these educational frameworks successfully facilitated high-value employability. The data demonstrated that the synergistic integration of these three mechanisms accounted for 61.2 percent of the variance in localized grassroots wealth creation. The findings confirmed that the domestic provision of international academic standards effectively transformed systemic brain drain into localized brain circulation. The study concluded that developing economies successfully engineered endogenous economic growth by strategically positioning transnational educational hubs as core engines for sustainable wealth creation.